1997
DOI: 10.1086/514556
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis and Kidney Disease in Patients with AIDS

Abstract: Renal disease in patients infected with human immunodeficiency virus (HIV) often presents with significant proteinuria and progressive renal failure; focal glomerulosclerosis is the most common renal pathology identified. To our knowledge, we report the first case of nephrotic-range proteinuria and preserved renal function in an HIV-infected patient in association with disseminated histoplasmosis. The initial level of proteinuria was 12.5 g/24 h. The patient developed a concomitant lesion on his neck, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 1 publication
3
16
0
Order By: Relevance
“…Several studies have shown the occurrence of hepatomegaly and/or high levels of AST and alanine aminotransferase in patients with histoplasmosis. 12,[14][15][16][17] Respiratory insufficiency is known to be a classic risk factor for death in patients with disseminated histoplasmosis, and this was confirmed in our study. Univariate analysis showed that serum creatinine levels > 1.5 mg/dL on hospital admission were associated with death.…”
supporting
confidence: 82%
“…Several studies have shown the occurrence of hepatomegaly and/or high levels of AST and alanine aminotransferase in patients with histoplasmosis. 12,[14][15][16][17] Respiratory insufficiency is known to be a classic risk factor for death in patients with disseminated histoplasmosis, and this was confirmed in our study. Univariate analysis showed that serum creatinine levels > 1.5 mg/dL on hospital admission were associated with death.…”
supporting
confidence: 82%
“…Bullock et al in 1979 reported a transient mesangiopathic glomerulonephritis in a patient with disseminated histoplasmosis and eosinophilia 14 . In another case report in 1997, Burke et al noted a nephrotic range proteinuria in a 46 year old HIV positive black man 13 who also had disseminated histoplasmosis. Renal biopsy in their patient demonstrated mesangio-proliferative glomerulonephritis.…”
Section: Discussionmentioning
confidence: 97%
“…It can also be immune complex mediated resulting in glomerulonephritis but it is rare 13 . Bullock et al in 1979 reported a transient mesangiopathic glomerulonephritis in a patient with disseminated histoplasmosis and eosinophilia 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Patients with CD4 counts of less than 150 cells/ µl are at increased risk. [14][15][16] Mucous membrane lesions are seen in disseminated histoplasmosis.…”
mentioning
confidence: 99%